Innovations in material science, applied mechanics, control and information technologies selected, peer reviewed papers from the 2014 2nd International Conference on Materials Science, Machinery and Energy Engineering (MSMEE 2014), November 7-8, 2014, Hong Kong - Yan, Guohui (Applied mechanics and materials, 2015)
Collection of selected, peer reviewed papers from the 2014 2nd International Conference on Materials Science, Machinery and Energy Engineering (MSMEE 2014), November 7-8, 2014, Hong Kong. The 21 papers are grouped as follows: Chapter 1: Materials Science; Chapter 2: Applied Mechanics, Modeling, Simulation and Control; Chapter 3: Data Processing and Information Technology